2014
DOI: 10.1111/oik.01219
|View full text |Cite
|
Sign up to set email alerts
|

Multitrophic diversity effects depend on consumer specialization and species‐specific growth and grazing rates

Abstract: Ecosystem functioning is affected by horizontal (within trophic groups) and vertical (across trophic levels) biodiversity. Theory predicts that the effects of vertical biodiversity depend on consumer specialization. In a microcosm experiment, we investigated ciliate consumer diversity and specialization effects on algal prey biovolume, evenness and composition, and on ciliate biovolume production. The experimental data was complemented by a process-based model further analyzing the ecological mechanisms behind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 43 publications
(69 reference statements)
1
25
0
Order By: Relevance
“…Indeed, studies have shown that predator‐induced prey suppression can induce compensatory population growth in prey species of faster regeneration (Filip et al. ; Thakur and Eisenhauer ), which may decrease prey evenness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, studies have shown that predator‐induced prey suppression can induce compensatory population growth in prey species of faster regeneration (Filip et al. ; Thakur and Eisenhauer ), which may decrease prey evenness.…”
Section: Discussionmentioning
confidence: 99%
“…Such results indicate that predators can alter prey community composition, that is, decreasing community evenness by favoring one prey over the other (Filip et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…It further showed that food web complexity could dampen trophic cascades, resulting to a decreased impact of predators on herbivores (Finke and Denno, 2004). In addition, species-specific traits, such as resource specialization, strongly affected prey biomass and diversity (Jiang and Morin, 2005;Filip et al, 2014) and induced shifts in trophic cascades (Steiner, 2001). Studies focusing on the combined effect of multiple predators with different resource utilization are unfortunately rare (Jiang and Morin, 2005;Diehl et al, 2013), but most likely better reflect natural communities and enable the direct observation of a major mediator of coexistence: resource partitioning (Chesson, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Although top-down and bottom-up effects that depend upon the specialization level of the consumer (Jiang and Morin, 2005;Filip et al, 2014) strongly affect system productivity and stability (Duffy et al, 2007;Jiang et al, 2009), a mechanistic understanding of these phenomena is still lacking. Early investigations focused on pairwise predatorprey interactions that were then generalized to complete communities under the assumption that multiple pairwise interactions had additive effects (Oksanen et al, 1981;Wootton, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…They indicated that these effects depend on species-specific traits that determine coexistence as well as ecosystem processes and functions (e.g. [4,5]). A number of different traits, such as body size, resource demand and acquisition, constrain fundamental abiotic niches as well as realized niches (coexistence), whereas the same (or additional) traits constrain species contributions to ecosystem functions.…”
Section: Introductionmentioning
confidence: 99%